(untitled) (Scientific journal of the Fergana State University, 2026)
The paper studies the influence of deep impurity levels on the photoelectric parameters of p-CdTe/n-CdS and p-CdTe/n-CdSe film heterostructures. The mechanisms of deep level formation during deposition and subsequent thermal treatment of layers are considered. It is established that the presence of deep levels significantly affects the processes of charge carrier recombination, reduces the lifetime of minority carriers and leads to a change in the spectral sensitivity of the structures. An analysis of the dependence of the main photoelectric characteristics - photocurrent, photovoltage and quantum yield - on the density and energy position of deep levels is given. The obtained results allow us to develop recommendations for optimizing the process parameters for creating highly efficient photoelectronic devices and solar cells based on p-CdTe/n-CdS and p-CdTe/n-CdSe heterostructures. It is determined that deep impurity levels in CdTe, the activation energy of which is equal to Ec=1.15 eV.